Phytochemical Investigation of Chamaemelum nobile L. and Evaluation of Acetylcholinesterase and Tyrosinase Inhibitory Activity - Luciana Maria Polcaro; Antonietta Cerulli; Milena Masullo; Sonia Piacente (Plants)
The ageing of the world population has led to an increase in the incidence of neurodegenerative diseases. In this regard, plants have become an important source of bioactive principles that are able to act on multiple targets. Chamaemelum nobile (L.) All. is a perennial herb of the Asteraceae family, known as Roman chamomile, less studied in the scientific literature than the more common Matricaria chamomilla. Flavonoids and sesquiterpene lactones represent the main secondary metabolites. Among these, nobilin and its derivatives are considered the main components. With the aim of performing a phytochemical investigation, the extract of the fresh aerial parts of C. nobile was firstly analysed by LC-(+)ESI/QExactive/MS/MS, which guided the isolation of 15 compounds (coumarins, glucoside derivatives, flavonoids, and germacrane-type sesquiterpene lactones) characterised by 1D and 2D NMR spectroscopy. The presence of a derivative of nobilin, never been reported before, was highlighted. Moreover, for all isolated compounds, acetylcholinesterase and tyrosinase inhibitory activity were tested by spectrophotometric assays. The results showed that the tested compounds presented interesting tyrosinase (IC50 values: 32.09–412.02 µM) and acetylcholinesterase inhibitory activity (IC50 values: 181.58–387.99 µM). In detail, apigenin 7-O-rutinoside (6) showed the highest tyrosinase and AchE inhibitory activity, with IC50 values of 32.09 and 181.58 µM, respectively.